Formulation of galactomannan microparticles as insulin carriers - Galrinho, Miguel Feijão (2023)
Insulin is a protein hormone responsible for various functions at the metabolic level. The deficiency of this hormone is compensated by subcutaneous administration which can bring discomfort. The pulmonary pathway shows potential as an alternative route, using microparticles as transporters. Galactomannans are polysaccharides with potential to be used as base material for microparticles preparation. In this work, locust bean gum (LBG) was used as a source of galactomannans. However, the high viscosity can bring some problems to the microparticle preparation. To reduce the viscosity, it was performed a microwave treatment (MW). Depolymerized LBG was fractionated by ultrafiltration allowing to obtain fractions of molecular weight >300 kDa (R300), 300-100 kDa (R100), 100-50 kDa (R50), 50-30 kDa (R30), 30-10 (R10) and <10 kDa (P10). Mannose and galactose were the main sugars identified in all samples, in agreement with the galactomannan composition. The ratio mannose:galactose varied between 3.3 and 4.0 showing that the branching degree was maintained. Insulin was added in a 1:10 (insulin:galactomannan, w/w) ratio to each fraction produced and spray-dried, forming particles. By scanning electron microscopy (SEM), “raisin-like” structures were observed in all samples with a variation on size distribution that allowed the denomination of microparticles. Fractions of higher molecular weight led to microparticles of 1-5 μm, considered to be within the respirable range, while the fraction of low molecular weight (30-10 kDa) led to microparticles with 92% in a 5-15 μm range, out of the required values for pulmonary delivery. Total insulin release occurred along 40 min in a linear way. The microparticles with 30-10 kDa material had a faster release, in only 20 min. The combination of MW, ultrafiltration and spray-drying techniques show potential for microparticle preparation for pulmonary delivery of insulin, where the speed of release can be controlled by the galactomannan dimensions.